A Chinese Herbal Formulation, Xiao-Er-An-Shen Decoction, Attenuates Tourette Syndrome, Possibly by Reversing Abnormal Changes in Neurotransmitter Levels and Enhancing Antioxidant Status in Mouse Brain - Chen, Jihang; Leong, Pou Kuan; Leung, Hoi Yan; Chan, Wing Man; Li, Zhonggui; Qiu, Jingyu; Ko, Kam Ming; Chen, Jianping (Frontiers in Pharmacology, 2019)
Xiao-Er-An-Shen Decoction (XEASD) has been used clinically for the treatment of Tourette syndrome (TS) in children for more than twenty years in Mainland China. The biochemical mechanism underlying the therapeutic action produced by XEASD treatment against TS remains unknown. However, a previous study has shown that pre-incubation of PC12 neuronal cells with XEASD can induce neurite outgrowth and protect against oxidative stress. In the present study, using a mouse model of TS induced by 3,3’-iminodipropionitrile (IDPN), XEASD treatment was found to significantly ameliorate the severity of behavioral symptoms in affected mice, as assessed by stereotypy scoring and locomotor activity. The beneficial effect of XEASD was accompanied by the reversal of abnormal levels of neurotransmitters, including striatal gamma-aminobutyric acid (GABA), glutamate and aspartate, in brain tissue of IDPN-challenged mice. In addition, XEASD treatment increased plasma cAMP levels and activated the phosphorylation of cAMP-responsive element binding protein (CREB) in brain tissue of TS mice. Furthermore, XEASD treatment was found to enhance the antioxidant status of brain tissue in affected mice, as evidenced by increases in the reduced glutathione/oxidized glutathione ratio and Mn-superoxide dismutase activity in brain mitochondrial fractions. Taken together, these experimental results will hopefully provide insight into the pharmacological basis for the beneficial effects of XEASD in children suffering from TS.